L'image de la Guerre civile espagnole dans la bande dessinée entre 1936 et 1975-II - Michel Matly (Cahiers de Civilisation Espagnole Contemporaine)
This paper is the second of two that present a quick overview of the representation of Spanish Civil War in comics from the beginning of the conflict in 1936 up to Franco's death in 1975. Meanwhile the first part was investigating Spanish comics during wartime, the present one deal with other countries' comics in the same period, as well as Spanish and foreign comics during the following years of the Francoist dictatorship. Afterwar, Spanish comics dedicated to the late conflict propagate dogmas of the Francoism and the Catholic church but face little audience. In other European countries, scarce comics also mostly back up Francoist thesis, and sympathy for the former Spanish Republic only may be met in American comics.